Lactobacillus thermotolerans sp. nov., a novel thermotolerant species isolated from chicken faeces - Niamsup P. (2014)
Five strains of thermotolerant lactic acid bacteria (G 12, G 22, G 35T, G 43 and G 44) isolated from chicken faeces were characterized taxonomically. The strains were facultatively anaerobic, Gram-positive, catalase-negative, non-motile, non-spore-forming rods. They were heterofermentative lactobacilli that produced DL-lactic acid. Growth of the strains occurred at 45°C but not at 15°C. The optimum temperature for growth was 42°C, as determined from the specific growth rate. The highest permissive temperatures for growth were 50°C for strain G 35T and 48°C for the other four strains. DNA G + C content of the strains was between 49 and 51 mol%. Complex fatty acid patterns of the strains showed the presence of C14:0, C16:0, sometimes C18:0, C18:1 and C19:0cyclo in the cell walls. Phylogenetic analysis of the 16S rRNA gene sequences of the five strains placed them in the Lactobacillus caseil Pediococcus group, with Lactobacillus fermentum as their closest relative (about 95% sequence similarity). DNA-DNA hybridization data indicated that the thermotolerant strains were not L. fermentum. Taken together, the findings of this study show that the five strains isolated from chicken faeces represent a novel species within the genus Lactobacillus, for which the name Lactobacillus thermotolerans is proposed (G 35T =DSM 14792T =JCM 11425T).